TEACHING ETHNOGRAPHIC RESEARCH METHODS IN SOCIAL WORK: A MODEL COURSE. - Sells, Scott P.; Smith, Thomas Edward; Newfield, Neal (Journal of Social Work Education)
The article presents a description of a social work course that incorporates instruction on ethnographic research. Six modules are presented that cover and include sampling strategies for data collection, data analysis, theory development, and presentation of findings. Module seven involves the application of these skills. Students are required to conduct an ethnographic evaluation of some area of social work practice from either the client's or the practitioner's perspective. Evaluations on the usefulness and relevance of this course were gathered from students completing it. The characteristics of all the seven course modules, used to teach students about ethnographic research methods, have been discussed in the article. The students' evaluation of the course supported the notion that it enhanced their ability to conduct and report on qualitative research studies, to think critically about practice conventions, and to evaluate and refine their practical skills. The educational and research implications of teaching ethnographic research methods within a social work curriculum, have been discussed.